Cyclopentitol as a scaffold for a natural product-like compound library for drug discovery. Issue 11 (1st June 2015) - Padwal, Jalindar D.; Filippov, Dmitri V.; Narhe, Bharat D.; Aertssen, Sjoerd; Beuving, Remmelt Jan; Benningshof, Jorg C.J.; van der Marel, Gijsbert A.; Overkleeft, Herman S.; van der Stelt, Mario
Graphical abstract: Abstract: A concise and efficient synthesis of cyclopentitols as a scaffold for a two-dimensional compound library for drug discovery is described. Starting fromd -mannose, the key steps are Wittig olefination and ring-closing metathesis (RCM) followed by a [3, 3]-sigmatropic Overmann rearrangement to form an sp 3 -rich, natural product-like scaffold from which a focused compound library with different functionalities is prepared.